IMPROVING READING AND WRITING LITERACY SKILLS THROUGH EXTENSIVE READING IN TANJUNG GUNDAP - Atun, Muslih; Siahaan, Safnidar; Adam, Adam; Marpaung, Junierissa; Subrata, Doni (English Department, University of Riau Kepulauan, Batam,Indonesia, 2025)
The purpose of this study was to use extensive reading approaches to improve the reading and writing literacy of teenagers in Tanjung Gundap, Batam. With 25 participants, the study used a one-group pretest-posttest methodology and a quantitative pre-experimental design. The study's main objective was to assess how well the skimming technique—a crucial tactic in lengthy reading—improves literacy. Twenty-item pre- and post-tests were used to gather data, and paired sample t-tests were used to compare the outcomes before and after the intervention. With a p-value of 0.000, the data from the pre-test and post-test revealed a significant difference in the students' reading and writing abilities. The post-test findings showed a movement toward higher literacy categories, with more children earning high and very high literacy scores. Before the intervention, most students had moderate to low reading levels. This study shows that reading widely, and using skimming strategies in particular, can improve literacy. According to the results, structured reading programs can significantly enhance students' academic performance, especially in the areas of writing and reading comprehension. In order to improve student learning results, the study highlights how crucial it is to incorporate comprehensive reading strategies into instructional procedures.